2021
DOI: 10.1108/ijse-11-2020-0747
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion, mobile banking, informal finance and financial exclusion: micro-level evidence from Morocco

Abstract: PurposeThis study has a dual purpose. The first is constructing a financial inclusion index to investigate if the reforms implemented during the last decades at the macroeconomic and sectoral levels have contributed to increase the financial inclusion level in Morocco. The second is to deepen the investigation to explore the impact of these reforms at the microeconomic level, by focusing on six major issues: determinants of financial inclusion, links between individual characteristics and barriers to financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
1
25
0
2
Order By: Relevance
“…( Ezzahid and Elouaourti, 2021) This manuscript tries to analyze the impact of digital banking on financial inclusion in Morocco.…”
Section: Paper Infomentioning
confidence: 99%
See 1 more Smart Citation
“…( Ezzahid and Elouaourti, 2021) This manuscript tries to analyze the impact of digital banking on financial inclusion in Morocco.…”
Section: Paper Infomentioning
confidence: 99%
“…This statement also supported by Aziz et al (2021) who investigated the correlation between digital banking and financial inclusion and found that digital banking has a positive correlation to financial inclusion. Moreover, Ezzahid & Elouaourti (2021) explained that digital banking plays a prominent role in reducing the number of unbanked by providing financial access in a convenient way and competitive price.…”
Section: Paper Infomentioning
confidence: 99%
“…Here, fintech adoption and leisure are investigated as integral components to improve the QoL of financially literate individuals. Previous studies on fintech focus on factors related to the intention to use (Daragmeh et al, 2021) and financial inclusion for unbanked citizens in developing regions (Ezzahid and Elouaourti, 2021). Incorporating Kass-Hanna et al (2022) argument that financial literacy needs to be redefined to include digital literacy, this study considers fintech adoption as an indicator of digital literacy.…”
Section: Financial Literacy and Quality Of Life 1713mentioning
confidence: 99%
“…Previous studies on fintech focus on factors related to the intention to use (Daragmeh et al. , 2021) and financial inclusion for unbanked citizens in developing regions (Ezzahid and Elouaourti, 2021). Incorporating Kass-Hanna et al.…”
Section: Introductionmentioning
confidence: 99%
“…In general, Microfinance can be defined as the provision of financial products and services to lowincome populations otherwise excluded from the access to formal financial services (Ezzahid & Elouaourti, 2021). For a long time, microfinance was considered an appropriate tool to simultaneously accomplish social and financial goals, and over time it has become more commercialized (Iqbal, 2018).…”
Section: Participative Finance Microfinance and Financial Inclusionmentioning
confidence: 99%